HUBUNGAN RIWAYAT KELUARGA DENGAN KEJADIAN KANKER PAYUDARA USIA MUDA DI RSUD ULIN BANJARMASIN - Zakia, Sukma Dina; Oktaviyanti, Ika Kustiyah; Budiwinata, Winardi; Rahman, Eka Yudha; Rosida, Lena (Universitas Lambung Mangkurat, 2024)
Abstract: Breast cancer is a malignant tumor that grows in breast tissue. Family history is the main risk factor for breast cancer because it plays a role in 5-10% of breast cancer cases. This is related to the inheritance of BRCA1 and BRCA2 gene mutations which are more often found at young ages compared to older ages. The research aims to analyze the relationship between family history and the incidence of breast cancer in young people at Ulin Hospital, Banjarmasin. Analytical observational research method, cross sectional design. The sample was taken as a total sampling of breast cancer patients who sought treatment at the Surgical Oncology Polyclinic, Ulin Banjarmasin Regional Hospital for the period January 2020-November 2023 according to the inclusion and exclusion criteria. Data was taken using a questionnaire and analyzed using Fisher's test. The results obtained were respondents who had a family history at a very young age (27.3%), young age (72.7%), who had no family history at a very young age (3.6%), young age (96.4%). ), p-value=0.034. The conclusion is that there is a significant relationship between family history and the incidence of breast cancer at a young age. Keywords: breast cancer, young age, family history. Abstrak: Kanker payudara adalah tumor ganas yang tumbuh dalam jaringan payudara. Riwayat keluarga merupakan faktor risiko utama kanker payudara dikarenakan berperan pada 5-10% kasus kanker payudara. Hal ini berkaitan dengan pewarisan mutasi gen BRCA1 dan BRCA2 yang lebih sering ditemukan pada usia muda dibandingkan usia yang lebih tua. Penelitian bertujuan untuk menganalisis hubungan riwayat keluarga dengan kejadian kanker payudara usia muda di RSUD Ulin Banjarmasin. Metode penelitian observasional analitik, desain cross sectional. Sampel diambil secara total sampling pasien kanker payudara yang berobat ke Poliklinik Bedah Onkologi RSUD Ulin Banjarmasin periode Januari 2020-November 2023 sesuai kriteria inklusi dan eksklusi. Data diambil menggunakan kuesioner dan dianalisis dengan uji Fisher. Hasil didapatkan responden yang memiliki riwayat keluarga pada usia sangat muda (27,3%), usia muda (72,7%), yang tidak memiliki riwayat keluarga pada usia sangat muda (3,6%), usia muda (96,4%), p-value=0,034. Kesimpulan terdapat hubungan yang bermakna antara riwayat keluarga dengan kejadian kanker payudara usia muda. Kata-kata kunci: kanker payudara, usia muda, riwayat keluarga.